Conflict of Local People and Larger Mammals - A Case of Chitwan National Park in Central Nepal - Timsina, Tatwa P (Journal of Advanced Academic Research, 2015)
Background: Chitwan National Park which covers 932 km2 lies in the lowlands or inner terai of southern central Nepal. It has 503 rhinoceros, 120 tigers and 40-50 elephants. Wildlife such as leopard, wild dog, sloth bear, gaur, sambar, chital, hog deer, barking deer, wild pig etc. are also found in this park. The park is facing enormous enroachment from the local people. Objective: The objective of this study is to study the causes of conflicts and find out the ways for park-people management. This study has been designed to reveal the intricate relationship among the large mammals and local people and the resultant conflict. Methodology: The study has applied cross-sectional design and included 100 people. Both the quantitative and qualitative approaches have been used to collect data. Research instruments namely interview, questionnaire and observation were applied for this study. Results: Larger mammals and local people have both positive and negative interactions. Negative interaction or conflict takes place due to the competition between the park and people that are concerned at crop damage, livestock loss and injury to rhino, deer, boar, tiger etc. Regarding the types of crops damaged by the wildlife, mustard, potato, maize, paddy and wheat top the list. Conclusion: In Chitwan National Park, the relation between larger mammals and local people is positive such as promoting tourism and maintaining greenery and negative in some cases such as injury and damage by larger mammals, restrictions on the use of park resources for local people etc. The park-people relationship can be managed by introducing a number of measures which respect the lives of both the local people and wildlife in the park. Both the park authorities and local people should work in coordination so that the benefit from the immeasurable gift of nature could be exploited. Journal of Advanced Academic Research Vol.1(1) 2014: 99-106